Environmental Issues of Destructive Megadroughts - Sarikulov, Madraim Khasanovich (American Journal of Biology and Natural Sciences, 2025)
This article examines the environmental issues of devastating megadroughts against the backdrop of air pollution and water shortages worldwide, as well as the state of the environment, which has begun to threaten the quality of life and the very existence of human society. The world is currently facing a growing threat – devastating megadroughts with prolonged periods of complete lack of precipitation that last for years. It is also noted that the drying up of lakes, which turn into lifeless expanses – deserts – is considered particularly dangerous.